Comparative analysis of body composition results of university students obtained using two bioimpedance analyzers - Peñaloza-Talavera Ma. Fidelina; Gonzalez-Correa Clara H.; Narvaez-Solarte William; Gomes-Santana-Pereira Izabella C.; Diaz-Vallejo Jhony A. (Journal of Electrical Bioimpedance)
Body composition is a key health indicator that distinguishes between fat mass and lean mass, factors associated with the risk of metabolic and cardiovascular diseases. Among measurement methods, bioelectrical impedance analysis (BIA) is widely used, with single- and multi-frequency devices showing differences in performance.